Interplay of anti‐SSA/SSB status and hypertension in determining cardiovascular risk in primary Sjögren's syndrome. (31st October 2019) - Bartoloni, E.; Baldini, C.; De Vita, S.; Priori, R.; Giacomelli, R.; Bini, V.; Gerli, R.
Abstract : Click here to view the Original article by Mofors et al.